The adequacy of Aboriginal Peoples Act 1954 pertaining to the land rights of Orang Asli / Nurul Natrah Mohd Saidi … [et al.] - Seman Ludin @ Kamaludin, Nuraini; Ahmad, Nurhafizah; Mohd Hazalli, Nurhuzaida; Mohd Saidi, Nurul Natrah; Ramzan, Zati Hanani (2010)
This research reviews the concept of adequate compensation pertaining to the acquisition of Orang Asli land and also their compensation regarding the plantation that they grow. The main focus is on the aspect of the inadequacy of the Aboriginal Peoples Act 1954 in protecting the Orang Asli. It also examines the practical approach in protecting the right of Orang Asli in the peninsular Malaysia regarding their land. Data and information is gathered from the interview that has been conducted and also from the case study that involve claim made by the Orang Asli. Firstly, this dissertation looks into the importance of customary land to the Orang Asli and why it is so significant to them. We will then further move on with the usual practice of a State Authority in acquiring the Orang Asli's land. After that, we will move ahead to discuss the effect of such acquiring process to the daily life of Orang Asli. In the end of this project paper, conclusion will be made and recommendations will be proposed based on the findings of the research with the hope to promote a better protection for the Orang Asli pertaining to their customary land.